Gender, Time Use, and Poverty in Sub-Saharan Africa - Blackden, C. Mark; Wodon, Quentin (Washington, DC: World Bank, 2012)
The papers in this volume examine the links between gender, time use, and poverty in Sub-Saharan Africa. They contribute to a broader definition of poverty to include time poverty, and to a broader definition of work to include household work. The papers present a conceptual framework linking both market and household work, review some of the available literature and surveys on time use in Africa, and use tools and approaches drawn from analysis of consumption-based poverty to develop the concept of a time poverty line and to examine linkages between time poverty, consumption poverty, and other dimensions of development in Africa such as education and child labor.